Percy Jackson & the Olympians [videorecording (DVD)] : the lightning thief - Columbus, Chris; Lerman, Logan, 1992-; Jackson, Brandon T., 1984-; Daddario, Alexandra, 1986-; Abel, Jake, 1987-; Bean, Sean; Brosnan, Pierce; Coogan, Steve; Dawson, Rosario; McKidd, Kevin; Thurman, Uma; Riordan, Rick (20th Century Fox Home Entertainment, 2010)
Percy Jackson is no ordinary teenager, he's the son of Poseidon and is accused of stealing Zeus' lightning bolt, the most powerful weapon ever created! With storm clouds brewing, Percy embarks on an incredible cross-country journey to prove his innocence, recover the bolt, and prevent a war among the gods that could destroy our world!